2008
DOI: 10.1186/1471-2407-8-242
|View full text |Cite
|
Sign up to set email alerts
|

Improved therapeutic effectiveness by combining liposomal honokiol with cisplatin in lung cancer model

Abstract: Background: Honokiol is a major bioactive compound extracted from Magnolia. The present study was designed to determine whether liposomal honokiol has the antitumor activity against human lung cancer as well as potentiates the antitumor activity of cisplatin in A549 lung cancer xenograft model, if so, to examine the possible mechanism in the phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 28 publications
(38 reference statements)
5
66
1
Order By: Relevance
“…In addition, honokiol has a more obvious apoptosis-inducing effect on B-CLL cells than on normal mononuclear leukocytes (40). In vivo, honokiol was highly effective against SVR angiosarcoma (41) and breast cancer in nude mice (42) and in a human A549 lung cancer xenograft model (43) with the increased induction of apoptosis.…”
Section: Targeting Apoptosis Pathways In Cancer With Magnolol and Honmentioning
confidence: 91%
“…In addition, honokiol has a more obvious apoptosis-inducing effect on B-CLL cells than on normal mononuclear leukocytes (40). In vivo, honokiol was highly effective against SVR angiosarcoma (41) and breast cancer in nude mice (42) and in a human A549 lung cancer xenograft model (43) with the increased induction of apoptosis.…”
Section: Targeting Apoptosis Pathways In Cancer With Magnolol and Honmentioning
confidence: 91%
“…36 In some studies, apoptosis has been demonstrated to occur weeks after cisplatin treatment. [37][38][39] In such experiments, it is not clear whether apoptosis is due to cisplatininduced signaling events or merely a passive effect [i.e., whether apoptosis is the primary cell death mechanism induced by druginduced signaling, or is a secondary effect induced by lethal cell damage (i.e. a ''funeral'' mechanism); see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with Barrett's-associated esophageal adenocarcinoma, furthermore, our finding that honokiol limits anchorage-independent growth in cancer cells suggests that this agent might be a useful cancer treatment. Other studies have shown that honokiol enhances the tumor-killing effects of a number of chemotherapeutic agents, including cisplatin, a drug used frequently in the treatment of esophageal adenocarcinoma (11,15).…”
Section: Discussionmentioning
confidence: 99%